Mechanism and regulation of mitophagy in liver diseases: a review - Liu, Sen; Wang, Libo; Zhu, Liuyang; Zhao, Tianyu; Han, Pinsheng; Yan, Fengying; Wang, Xiaoliang; Li, Chunli; Wang, Ze; Yang, Bao-feng (Frontiers in Cell and Developmental Biology, 2025)
Mitochondria are vital for the proper operation of healthy eukaryotic cells. Mitophagy, a specialized form of autophagy that targets damaged or surplus mitochondria, plays a key role in both the normal functioning and disease-related processes within the liver. This review aims to explore the main mechanisms underlying the initiation of mitophagy and its importance in various liver conditions, such as alcoholic liver disease, drug-induced liver injury, non-alcoholic fatty liver disease, viral hepatitis, and cancer. Gaining insight into these mechanisms can help overcome the obstacles related to harnessing mitophagy as a therapeutic strategy in clinical practice.